Private pesticide application complaints - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet discusses the process of a private pesticide application complaint in Colorado.
CEPEP 5/03, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticide applicators (Persons) -- Colorado; Complaints (Administrative procedure) -- Colorado